TERAPI GEN PADA PERAWATAN PERIODONTITIS DAN PERI-IMPLANTITIS : A REVIEW DAN IMPLIKASI MASA DEPAN - Muhammad Yudin; Sri Oktawati (Universitas Baiturrahmah, 2021)
Introduction: Periodontal disease is a chronic inflammatory condition that affects supporting tissue around the teeth which results in periodontal tissue damage. If left untreated, periodontal disease can cause tooth loss. When this condition occurs around dental implants, the disease is called peri-implantitis. Along with the development of science and technology, various treatments for periodontitis and peri-implantitis have also been found. One of them is gene therapy. Gene therapy is a treatment that is offered and is proven to provide maximum results. Therefore, in this review, we present gene therapy in the application of periodontal tissue and peri-implant regeneration. The purpose of this article is to review the literature on the current of gene therapy in treatment of periodontitis dan peri-implantitis. Review: Periodontitis and peri-implantitis treatment with gene therapy is based on treatment by transferring genetic material to introduce, suppress, or manipulate certain genes that direct a person to have his own cells to produce therapeutic agents. Gen therapy can achieve greater bioavability of growth factors in periodontal wound so that they have greater regenerative potential, both in-vivo and ex-vivo with viral and non-viral vectors. Conclusion: Within the limitation of this review, it was shown that gene therapy could be an alternative in overcoming the weakness of various growth factors and showed promising results.